The relationships among motivation, self-efficacy beliefs and use of self-regulated learning strategies : A comparative study of learners of English and Spanish - Valtonen, Saara (My University, 2021)
The purpose of the study was to examine the differences in self-efficacy beliefs, motivation and use of self-regulated learning strategies between two groups of language learners, namely learners of English and learners of Spanish. The second aim of the study was to examine the connections between the language learners’ reported self-efficacy beliefs, motivation and strategy use. The participants of the present study were 81 ninth-graders, 62 of whom were learners of English and 19 of whom learners of Spanish. Both quantitative and qualitative methods were used for data collection and analysis. The instrument used was a questionnaire measuring the participants’ perceived self-efficacy, level of motivation and frequency of strategy use, which consisted of Likert-scale items and open-ended questions. In order to provide more insight into the examined factors, qualitative data was also collected through seven semi-structured interviews. According to the results, the learners of Spanish reported a lower level of self-efficacy beliefs compared to the English group, but no significant differences were found between the two groups in terms of motivation or strategy use. On average, both groups reported high levels of motivation and occasional use of self-regulated language learning strategies. As for the relationships between the three examined variables, strong, positive, and statistically significant relationships were found between self-efficacy and motivation, and between motivation and strategy use, as well as a moderate connection between self-efficacy and strategy use in both groups, although the results of the Spanish group turned out to not be highly reliable due to the small sample size. Future studies examining these factors should be carried out with larger samples of randomly selected participants. The findings of this study point towards a reciprocal relationship between learners’ self-efficacy beliefs, motivation and their self-regulated learning behavior. The qualitative data further elucidated that each student’s self-efficacy beliefs influenced their level and type of L2 motivation, as well as the effort they were willing to invest in their learning, thus also affecting their self-regulatory behavior regarding their L2 learning. It can be extrapolated from these findings that enhancing L2 learners’ self-efficacy beliefs, motivation and strategy use is crucial in helping them develop this beneficial circle of self-regulation.
Keywords: self-efficacy, self-regulated learning, language learning strategies, motivation